ANALISIS MINAT MAHASISWA TERHADAP KEWIRAUSAHAAN DENGAN KEINGINAN KERJA MAHASISWA SETELAH LULUS PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS PEKALONGAN - Dwi Susilo; Kartono Muhammad (LPPM Universitas Pekalongan, 2012)
The purposes of the research are : How many student university of management study program who are interested in enterprenuership, The need of work after their graduation and how many student who are needs in enterprenuership. The interest effect of student university towards the need of their work, with the 90 sample of student the results of the research are : 47 or 52% sample of student university interest in public servant or private official, 54 or 60% sample of student university the want to be of enterprenuer after their graduation. Asymp. Sig (2-sided) in Pearson Chi-Square that is 0,730 more than 0,05, So, there is not correlation and not effect between the interest and their need of working sample of student university after graduation. The Keywords : Interest, Need and Enterprenuership.